Three-dimensional network graphene oxide/sodium alginate aerogel beads with slit-shaped structure: Synthesis, performance and selective adsorption mechanism for Cu(II). Issue 6 (December 2021) - Ji, Cheng; Yang, Shuyi; E, Tao; Cheng, Ying; Hao, Xin; Li, You
Abstract: Based on cross-linking and freeze-drying methods, a three-dimensional network graphene oxide/sodium alginate aerogel beads (GSC) is prepared to selectively adsorb Cu(Ⅱ) in aqueous solution, with a slit-shaped structure. According to the results of characterizations, it suggests that the slit-shaped structure is formed via the stacking of GO sheets, and GO participates in the cross-linking reaction between Ca and SA connecting by Ca-carboxyl and Ca-hydroxy, as well as intermolecular hydrogen bonds between GO and SA. Furthermore, batch adsorption experiments and Design of Experiment (DOE) show that GSC has excellent adsorption capacity and reusability, and pH is the main factor that affects the adsorption performance of GSC. Importantly, the slit-shaped structure of GSC can still selectively adsorb plane quadrilateral [Cu(H2 O)4 ] 2+ in the presence of interfering ions (Zn(II), Mn(II) and Cr(Ⅲ)). The fitting results of adsorption kinetics and isotherm model prove that the adsorption process is mainly multi-layer adsorption and chemical adsorption. Additionally, the mechanism is explored using the method of Density functional theory (DFT), revealing that -COOH, -O-, -OH on GO play important roles in adsorbing Cu(Ⅱ), and the order of is: -COOH > -O- > -OH. Graphical Abstract: ga1 Highlights: A three-dimensional network-GSC with a slit-type structure was prepared. The slit structure of GSC has selective adsorption to planar hydrated ion Cu(Ⅱ). The adsorption of Cu(Ⅱ) by GO is dominant in GSC. Adsorption capacity of functional groups is in the order of: -COOH > -O- > -OH.